Back and forth from cool core to non-cool core: clues from radio halos - Rossetti, M.; Eckert, D.; Cavalleri, B. M.; Molendi, S.; Gastaldello, F.; Ghizzardi, S. (Astronomy and astrophysics (Berlin), 2011)
X-ray astronomers often divide galaxy clusters into two classes: “cool core” (CC) and “non-cool core” (NCC) objects. The origin of this dichotomy has been the subject of debate in recent years, between “evolutionary” models (where clusters can evolve from CC to NCC, mainly through mergers) and “primordial” models (where the state of the cluster is fixed “ab initio” by early mergers or pre-heating). We found that in a well-defined sample (clusters in the GMRT Radio halo survey with available Chandra or XMM-Newton data), none of the objects hosting a giant radio halo can be classified as a cool core. This result suggests that the main mechanisms that can start a large-scale synchrotron emission (most likely mergers) are the same as those that can destroy CC, which therefore strongly supports “evolutionary” models of the CC-NCC dichotomy. Moreover, combining the number of objects in the CC and NCC state with the number of objects with and without a radio-halo, we estimated that the time scale over which a NCC cluster relaxes to the CC state should be larger than the typical life-time of radio-halos and likely shorter than  ≃3 Gyr. This suggests that NCC transform into CC more rapidly than predicted from the cooling time, which is about 10 Gyr in NCC systems, allowing the possibility of a cyclical evolution between the CC and NCC states.